Pregnancy Complications and Long-Term Mortality in a Diverse Cohort. Issue 13 (8th March 2023) - Hinkle, Stefanie N.; Schisterman, Enrique F.; Liu, Danping; Pollack, Anna Z.; Yeung, Edwina H.; Mumford, Sunni L.; Grantz, Katherine L.; Qiao, Yan; Perkins, Neil J.; Mills, James L.; Mendola, Pauline; Zhang, Cuilin
Abstract : Background: Pregnancy complications are associated with increased risk of development of cardiometabolic diseases and earlier mortality. However, much of the previous research has been limited to White pregnant participants. We aimed to investigate pregnancy complications in association with total and cause-specific mortality in a racially diverse cohort and evaluate whether associations differ between Black and White pregnant participants. Methods: The Collaborative Perinatal Project was a prospective cohort study of 48 197 pregnant participants at 12 US clinical centers (1959–1966). The Collaborative Perinatal Project Mortality Linkage Study ascertained participants' vital status through 2016 with linkage to the National Death Index and Social Security Death Master File. Adjusted hazard ratios (aHRs) for underlying all-cause and cause-specific mortality were estimated for preterm delivery (PTD), hypertensive disorders of pregnancy, and gestational diabetes/impaired glucose tolerance (GDM/IGT) using Cox models adjusted for age, prepregnancy body mass index, smoking, race and ethnicity, previous pregnancies, marital status, income, education, previous medical conditions, site, and year. Results: Among 46 551 participants, 45% (21 107 of 46 551) were Black, and 46% (21 502 of 46 551) were White. The median time between the index pregnancy and death/censoring was 52 years (interquartile range, 45–54). Mortality was higher among Black (8714 of 21 107 [41%]) compared with White (8019 of 21 502 [37%]) participants. Overall, 15% (6753 of 43 969) of participants had PTD, 5% (2155 of 45 897) had hypertensive disorders of pregnancy, and 1% (540 of 45 890) had GDM/IGT. PTD incidence was higher in Black (4145 of 20 288 [20%]) compared with White (1941 of 19 963 [10%]) participants. The following were associated with all-cause mortality: preterm spontaneous labor (aHR, 1.07 [95% CI, 1.03–1.1]); preterm premature rupture of membranes (aHR, 1.23 [1.05–1.44]); preterm induced labor (aHR, 1.31 [1.03–1.66]); preterm prelabor cesarean delivery (aHR, 2.09 [1.75–2.48]) compared with full-term delivery; gestational hypertension (aHR, 1.09 [0.97–1.22]); preeclampsia or eclampsia (aHR, 1.14 [0.99–1.32]) and superimposed preeclampsia or eclampsia (aHR, 1.32 [1.20–1.46]) compared with normotensive; and GDM/IGT (aHR, 1.14 [1.00–1.30]) compared with normoglycemic. P values for effect modification between Black and White participants for PTD, hypertensive disorders of pregnancy, and GDM/IGT were 0.009, 0.05, and 0.92, respectively. Preterm induced labor was associated with greater mortality risk among Black (aHR, 1.64 [1.10–2.46]) compared with White (aHR, 1.29 [0.97–1.73]) participants, while preterm prelabor cesarean delivery was higher in White (aHR, 2.34 [1.90–2.90]) compared with Black (aHR, 1.40 [1.00–1.96]) participants. Conclusions: In this large, diverse US cohort, pregnancy complications were associated with higher mortality nearly 50 years later. Higher incidence of some complications in Black individuals and differential associations with mortality risk suggest that disparities in pregnancy health may have life-long implications for earlier mortality.